Development, Characterization, and Pharmacodynamic Evaluation of Hydrochlorothiazide Loaded Self-Nanoemulsifying Drug Delivery Systems - Pankajkumar S. Yadav (The Scientific World Journal, 2014)
The objective of the current work was to develop optimized self-nanoemulsifying drug delivery systems (SNEDDS) and evaluate their in vitro and in vivo performance. The research comprised various studies which includes solubility studies in various vehicles, pseudoternary phase diagram construction, and preparation and characterization of SNEDDS along with in vitro dissolution and in vivo pharmacodynamic profiling. Based on dissolution profile, a remarkable increase in rate of dissolution was observed in comparison with plain drug and marketed formulation. Optimized SNEDDS formulation was composed of Capmul MCM (19.17% w/w), Tween 80 (57.5% w/w), Transcutol P (12.7% w/w), and HCT (4.17% w/w). In vivo pharmacodynamic evaluation in Wistar rats showed considerable increase in pharmacological effect of HCT by SNEDDS formulation as compared with plain HCT.